Good laboratory practice OECD principles and guidance for compliance monitoring. (OECD, 2005)
This publication unites all of the OECD documents related to Good Laboratory Practice and compliance monitoring, and, in the Annex, reproduces the three OECD Council Decisions related to the Mutual Acceptance of Data in the Assessment of Chemicals. It includes the international standards for quality of non-clinical environmental, health and safety data on chemicals and chemical products in a regulatory context--the OECD Principles of Good Laboratory Practice--and supporting Consensus and Advisory Documents on their interpretation and application. The OECD guidance documents for governments on monitoring compliance with the Good Laboratory Practice Principles are also included. This publication thus presents the state of the art on Good Laboratory Practice and compliance monitoring.
Published also in French under title: Les bonnes pratiques de laboratoire : principes de l'OCDE et directives pour évaluer leur respect.
"Cancels and replaces the original Principles adopted in 1981"--Page [7].
1981 Principles published in 1982 under title: Good laboratory practice in the testing of chemicals.
Keywords: Chemical laboratories -- Quality control.; Laboratories -- Quality control.; elektronické knihy; electronic books